Edukasi Pencegahan Penyakit Tuberkulosis (TBC) dan Stunting pada Anak sebagai Upaya Pemberdayaan Masyarakat di Bojongloa Kidulkota Bandung - Juliyanti Juliyanti; Linda Hotmaida; Widawati Widawati; Yohanes Adi Bangun Wiratmo; Ancilla Linna Limenna; Yuliani Yuliani; Ria Angelina (Jurnal Kabar Masyarakat, 2026)
Tuberculosis (TB) and stunting remain serious public health challenges in Indonesia, particularly in densely populated urban areas. RW 05 Situsaeur Urban Village, Bojongloa Kidul Subdistrict, Bandung City is an area with a high risk of TB transmission and undernutrition among children under five, while community understanding of early TB symptoms, transmission routes, balanced nutrition, and stunting prevention remains limited. This community service activity aimed to improve community knowledge, attitudes, and behavior in preventing TB and stunting in children through health education and cadre empowerment. The activity was conducted on 2 December 2025 at the Dojo Building of RW 05 Situsaeur, involving 42 participants consisting of mothers of children under five, Posyandu cadres, and community leaders. Methods included interactive health education, educational videos, focus group discussions, demonstrations of effective coughing technique and nutritious complementary feeding (MPASI) preparation, and distribution of leaflets and posters. Evaluation was conducted using pretest and posttest. Results showed an increase in knowledge across all measured indicators: early TB symptoms in children (67% to 74%), TB transmission routes (69% to 74%), balanced nutrition principles (66% to 69%), and stunting prevention methods (63% to 88%). Posyandu cadres expressed readiness to continue similar education independently using the provided materials. This activity demonstrates that interactive education combined with cadre empowerment is an effective and sustainable strategy for community-level TB and stunting prevention.